Achieving triple bottom line outcomes through strategic reputation management: A role for communications leadership - Bolen, Haley (My University, 2023)
This research paper discusses the opportunities for communicators to lead organizations into a new era of stakeholder capitalism within a changing business landscape. Specifically, it explores how companies who hold a triple bottom line (TBL) mandate use strategic reputation management to achieve success in performance management that includes social, environmental, and financial outcomes. This research explores a relationship between strategic reputation management and triple bottom line outcomes wherein reputation management is elevated as a strategic function that leverages an orientation toward stakeholders to support social, environmental, and financial outcomes. Likewise, a focus on triple bottom line, or related frameworks like corporate social responsibility, and ESG (environmental, social, and governance) can help enhance reputation as a direct outcome for organizations. The paper builds upon existing research in the fields of business management, stakeholder theory, public relations theory, and strategic communications. The research examines 10 leading Canadian companies through primary and secondary data collection of corporate publications and in-depth interviews and employs thematic analysis to explore the relationship between the research concepts. The results show five thematic categories that address the research objective of establishing how and to what extent companies who pursue a triple bottom line institutionalize a stakeholder orientation and how they employ strategic reputation management. This research finds the contributions of strategic reputation management to TBL outcomes are centred around two-way symmetrical communications, relationship building, co-orientation with diverse stakeholders, and enterprise integration of a balanced valuation of people, planet, and profit. Given that the tactics connecting these concepts are best executed by communications leaders, this paper presents a framework for adoption by communications leaders in other companies. This research contributes to the literature and to the practice of strategic communications, reputation management, and stakeholder capitalism in business management.